What Matters for Educated and Uneducated Indian Women: Realizing Identity Struggle for Self and Matriarchal Harmony through Shashi Deshpande’s That Long Silence - Ramasamy, Ragupathi; Pavithra, B.; Joseph, Jennifer G; Tharini, C; B, Geetha; Sharmila, Maria Sahaya (Journal of Ecohumanism, 2024)
This article is an attempt to explore the challenges faced by educated and uneducated Indian women and the kind of silence and secrecy they maintain in the patriarchal society in search of self-identity. At the outset, it is worth emphasizing that men have traditionally been claiming a superior status in Indian Society and women have not been able to find equal face in affairs pertaining to family and society. This paper engages with the ways in which women characters are illustrated and how they are compelled by both the genders to remain voiceless in accepting their lot. The major focus of this article is to throw light on Shashi Deshpande’s views about Indian woman brought up under a traditional set up. The novelist’s diligence in story telling is very much evident in the manner in which the protagonist, Jaya, is portrayed in novel That Long Silence. It is pertinent to note that by virtue of her resilience and abilities, Jaya is able to establish an identity overcoming the challenges imposed on her by the family and society.